Marriage proposals : questioning a legal status - Bernstein, Anita (New York University Press, 2006)
The essays in Marriage Proposals envision a variety of scenarios in which adults would continue to join themselves together seeking permanent companionship and sustenance, linking sexual intimacy to a long commitment, usually caring for each other, and building new families. What would disappear are the legal consequences associated with marriage. No joint income tax return; no immigration privileges like the "fiancée visa" or the right to bring in a husband or wife; no special statuses for prison visits or hospital decisions; no prerogative to remain silent in court by claiming "confidential.